2006
DOI: 10.1016/j.ijpsycho.2006.05.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of graded monetary reward on cognitive event-related potentials and behavior in young healthy adults

Abstract: Temporal correlates of the brain circuit underlying reward processing in healthy adults remain unclear. The current study investigated the P3 and contingent negative variation (CNV) as putative reward-related temporal markers. The effect of sustained monetary reward on these event-related potentials and on behavior was assessed using a warned reaction-time paradigm in 16 young healthy subjects. Monetary reward (0, 1 and 45 cents) varied across blocks of trials. While the CNV was unaffected by money, P3 amplitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
134
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 42 publications
31
134
1
Order By: Relevance
“…Thus, the neural activity required for the successful preparation (here, encoding) of an upcoming event seems to be enhanced by the motivation to gain reward. This modulation of the P3b by reward expectancy is in line with results from other studies showing larger P3b amplitudes for reward trials than for trials without reward (Begleiter, Chou, & Aunon, 1983;Krebs et al, 2013;Parvaz, Konova, Tomasi, Volkow, & Goldstein, 2012), as well as for high-as compared to lowreward conditions (Capa, Bouquet, Dreher, & Dufur, 2013;Goldstein et al, 2006). Recently, Krebs and colleagues applied a Stroop task and found increased P3b amplitudes to reward-predicting cues, which were interpreted as increased preparatory attention toward critical features of the upcoming Stroop stimulus that were essential to obtain later reward.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…Thus, the neural activity required for the successful preparation (here, encoding) of an upcoming event seems to be enhanced by the motivation to gain reward. This modulation of the P3b by reward expectancy is in line with results from other studies showing larger P3b amplitudes for reward trials than for trials without reward (Begleiter, Chou, & Aunon, 1983;Krebs et al, 2013;Parvaz, Konova, Tomasi, Volkow, & Goldstein, 2012), as well as for high-as compared to lowreward conditions (Capa, Bouquet, Dreher, & Dufur, 2013;Goldstein et al, 2006). Recently, Krebs and colleagues applied a Stroop task and found increased P3b amplitudes to reward-predicting cues, which were interpreted as increased preparatory attention toward critical features of the upcoming Stroop stimulus that were essential to obtain later reward.…”
Section: Introductionsupporting
confidence: 87%
“…Furthermore, in a task-switching paradigm, larger P3b amplitudes during response execution on reward trials were associated with a greater investment in WM benefiting fast reaction times (Capa et al, 2013). In addition, the CNV has also been shown to be linked to reward expectancy, since trials indicating reward for fast and correct responses produced larger CNV amplitudes (Capa et al, 2013;Falkenstein, Hoormann, Hohnsbein, & Kleinsorge, 2003; but see Goldstein et al, 2006 Krebs et al, 2013; or the sustained potential [SP] by West & Alain, 2000;West et al, 2005), in that they peaked earlier during trials with than in those without reward, where no amplitude differences were reported. This temporal shift has been interpreted as an earlier start of conflict processing, which was triggered by enhanced attention toward relevant features of the Stroop stimulus, linked to the preceding P3b in Krebs et al's study.…”
Section: Introductionmentioning
confidence: 98%
“…For example, Pierson et al (1987) used a conditioning paradigm in which participants learnt to differentiate between one of three tone stimuli signalling gain, loss and neutral conditions; whilst Goldstein and colleagues (2006) focused on the effect of varying levels of monetary incentive. Goldstein et al (2006) note that differential sensitivity to reward may arise due to personality trait differences amongst participants and, similarly, Pierson et al (1987) found a larger effect in hedonic compared with anhedonic participants, suggesting that individual differences in the ability to experience pleasure may influence the sensitivity of the CNV to reinforcement. In the current study, the enhanced CNV response to Delay Escape relative to Delay No-Escape cues did not differ between time-windows (i.e.…”
Section: Discussionmentioning
confidence: 85%
“…Despite its commonly observed role in effortful preparation (Brunia et al, 2011;Cant & Bickford, 1967;Van Boxtel & Bocker, 2004), there has been less focus on the CNV in relation to reinforcement and no studies relating to negative reinforcers such as delay. Although there is some evidence that the CNV is modulated by positive reinforcers such as monetary reward (Pierson, et al, 1987), more recent work has not replicated this finding (Goldstein, et al, 2006;Goldstein, et al, 2008). The discrepancy between these results might be due to differences between paradigms.…”
Section: Discussionmentioning
confidence: 91%
“…Within these constraints, we further aimed to inspect differences between the highest and lowest rewards 1 Note that in our previous study these two fractal images had no significant differential effects on the selected ERP components, which included the P300 (Goldstein et al, 2006).…”
Section: Taskmentioning
confidence: 99%